2007
DOI: 10.1017/s0272263107070040
|View full text |Cite
|
Sign up to set email alerts
|

OPERATIONAL DEFINITIONS OF EXPLICIT AND IMPLICIT KNOWLEDGE: Response to R. Ellis (2005) and Some Recommendations for Future Research in This Area

Abstract: This article comprises two parts. The first part is a critique of R. Ellis's (2005) psychometric study, which attempted to use an exploratory factor analysis (EFA) to establish operationalizations of the constructs of explicit and implicit knowledge. I argue that the choice of an EFA in this endeavor is misguided and that a confirmatory factor analysis should have been employed. Additionally, the specific execution of the EFA is criticized on a number of fronts. The major claim of the critique is that R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…R. Ellis interpreted the two factors as analogous to implicit and explicit L2 knowledge, respectively. In response to the critique by Isemonger () that confirmatory rather than exploratory factor analysis would have been a more appropriate choice in a verificational study, R. Ellis and Loewen () reanalyzed the data reported in R. Ellis () using confirmatory factor analysis. The results confirmed the two‐factor model with the elicited oral imitation task, the oral narration task, and the timed grammaticality judgment test loading on one factor and the untimed grammaticality judgment test and the metalinguistic knowledge test loading on the other.…”
Section: Introductionmentioning
confidence: 99%
“…R. Ellis interpreted the two factors as analogous to implicit and explicit L2 knowledge, respectively. In response to the critique by Isemonger () that confirmatory rather than exploratory factor analysis would have been a more appropriate choice in a verificational study, R. Ellis and Loewen () reanalyzed the data reported in R. Ellis () using confirmatory factor analysis. The results confirmed the two‐factor model with the elicited oral imitation task, the oral narration task, and the timed grammaticality judgment test loading on one factor and the untimed grammaticality judgment test and the metalinguistic knowledge test loading on the other.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies have identified numerous sources and causes for the production and perception of FA in L2 speech: different acquisition scenarios, i.e. simultaneous multilingualism/bilingualism (Genesee, 2000; Meisel, 2001, 2004) vs. sequential multilingualism/bilingualism (Lakshmanan, 1994; McLaughlin, 1978),the mode of language learning (instructed vs. naturalistic language learning, DeKeyser, 2003; Ellis, 2006, 2007; Isemonger, 2007), andother external factors including sociological and cultural background, situational, contextual and procedural variables and learner-specific factors (including cognitive, motivational and emotional factors and personality traits, Bayley & Langman, 2004; Bayley & Regan, 2004; Dewaele, 2004; Dörnyei, 2009, Flege, Birdsong, Bialystok, Mack, Sung & Tsukada, 2006; Major, 2004; see Piske, MacKay & Flege, 2001, for an overview).…”
Section: Introductionmentioning
confidence: 99%
“…the mode of language learning (instructed vs. naturalistic language learning, DeKeyser, 2003; Ellis, 2006, 2007; Isemonger, 2007), and…”
Section: Introductionmentioning
confidence: 99%
“…critiquesEllis' (2005) use of statistical procedures and criticizes his use of exploratory factor analysis to investigate the constructs of implicit and explicit L2 knowledge. He suggests the use of confirmatory factor analysis or structural equation modeling as more appropriate in this instance, as well as for future research 2007. Ellis, R. & S. Loewen(2007).…”
mentioning
confidence: 99%
“…He suggests the use of confirmatory factor analysis or structural equation modeling as more appropriate in this instance, as well as for future research 2007. Ellis, R. & S. Loewen(2007). Confirming the operational definitions of explicit and implicit knowledge inEllis (2005): Responding to Isemonger.…”
mentioning
confidence: 99%